Can self‐compassion help us better understand the impact of pulmonary hypertension on those with the condition and their carers? A cross‐sectional analysis. (15th March 2023) - Rawlings, Gregg H.; Novakova, Barbora; Armstrong, Iain; Thompson, Andrew R.
Abstract: Pulmonary hypertension (PH) can have a multifaced impact both on the affected individual and close family members. However there are relatively few studies that have sought to identify potential protective factors. Individual differences in ability to be self‐compassionate are known to be implicated in adjustment in other long‐term conditions and are now featuring in the provision of care for a number of conditions. This is a cross‐sectional study that investigated the relationship between self‐compassion, demographic, PH‐related information, and measures of psychosocial functioning in adults with PH ( n  = 65) and caregivers ( n  = 29). Individuals with PH and caregivers of someone with PH completed self‐report measures on demographic and clinical factors, anxiety, depression, self‐compassion, and in those with PH, health‐related quality of life, and in carers, caregiver burden. Data were analyzed using hierarchical regression analyses. Surprisingly, participants with PH and caregivers did not significantly differ on rates of depression ( p  = 0.19) or anxiety ( p  = 0.57) with both scoring relatively high. Components of self‐compassion were associated with psychological functioning in both individuals and caregivers. Greater self‐compassion was associated with fewer symptoms of anxiety and depression, and greater health‐related quality of life in individuals with PH and lower burden in caregivers. More specifically, multiple regression analyses revealed after controlling for age, gender, and duration of PH, self‐compassion was a significant predictor of anxiety and depression in people with PH, and of anxiety and caregiver burden in carers. These findings add to the evidence base indicating that there can be a range of burdens experienced by both people living with PH and their wider families. Further, this study uniquely suggests that psychological and supportive interventions that seek to build self‐compassion may be useful to develop and test in this clinical group.